Teacher Candidates Collaborate to Create Place-Based Integrated Curriculum - Amanda Wall; Taylor Norman (Middle Grades Review, 2021)
A small group of middle level teacher candidates collaborated to create place-based integrated curriculum. These candidates and the authors, two teacher educators, selected two local sites, visited them together, and debriefed these visits. State and national standards as well as guidelines for integrated curriculum (e.g., Beane, 1997; Nesin & Lounsbury, 1999) informed the process. Through interpretive phenomenology analysis (Smith et al., 2009), we analyzed place-based learning as a catalyst for collaboration. Teacher candidates recognized possibilities with place-based learning to draw on local cultural, historical, and natural resources in ways that are relevant to students and their communities. We offer implications for teacher educators and middle level educators invested in place-based pedagogies and curricula.
Keywords: curriculum integration; place-based learning; teacher candidates; collaboration